The Water Sensitive Future of Lahijan - Mirsafa, Masoumeh (TeMA - Journal of Land Use, Mobility and Environment, 2017)
The emergence of the modern urban water system in Iran, albeit facilitated access to clean water and accelerated discharge of waste- and stormwater, it left some negative imprints on country’s urban and natural environment. Among which larger stress on natural water cycles and pollution of water resources are of great importance. More importantly, such impacts are occurring when cities are going through a changing climate, and are facing higher risks of water shortages and flooded urban surfaces in warm and wet seasons, respectively. The present research is built upon a case study conducted in Lahijan, a small city in northern Iran. Bridging between traditional urban design principles and water management practices, the study aims to find ways to connect place making with urban water infrastructure design in order to reintegrate water into the design of public spaces to create visually pleasant, environmentally sustainable and yet resilient contemporary urban forms. The analysis of the water-state of the traditional city reveals that stormwater has been an integrated into the design of Lahijan’s public spaces for centuries, and that the blue and green surfaces were the key components in constructing the porous landscape of Lahijan. As an endeavor to build new techniques upon the old traditions, the paper concludes that after a long period of absence of water in urban settings, water must be reintegrated in the design of public spaces. Accordingly, urban spaces of the future water sensitive Lahijan through various storage, conveyance, infiltration, and evaporation capacities shape the distributed on-site stormwater management infrastructure of the city which can adapt to the impacts of a changing environment while addressing the problems of water scarcity, flooding, and pollution.